1997
DOI: 10.1038/sj.leu.2400874
|View full text |Cite
|
Sign up to set email alerts
|

Four aged siblings with B cell chronic lymphocytic leukemia

Abstract: All four aged siblings (Ͼ80 years) of one family presented with B cell chronic lymphocytic leukemia (B-CLL). In an attempt to find common characteristics in the four patients, we performed detailed immunological marker analysis, Southern blot analysis of immunoglobulin (Ig) genes, and cytogenetic studies. In three patients clonality of the B-cells could be proven by single Ig light chain expression, but in the fourth patient no Ig light chain expression was detected and clonality of the B cells could only be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Over 70 pedigrees have been reported (most recently last year 11 ) over the last seven decades describing the clustering in families of CLL and, sometimes, other lymphoproliferative disorders. Although early reports on familial CLL were described before B cells had been described, most of the diagnoses are likely to be accurate since diagnosis of CLL may be distinguished from other leukaemias on clinical and morphological grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Over 70 pedigrees have been reported (most recently last year 11 ) over the last seven decades describing the clustering in families of CLL and, sometimes, other lymphoproliferative disorders. Although early reports on familial CLL were described before B cells had been described, most of the diagnoses are likely to be accurate since diagnosis of CLL may be distinguished from other leukaemias on clinical and morphological grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary factors appear to be a major contributing determinant in a subset of CLL cases. Several studies have shown evidence of familial clustering of CLL in siblings [Cartwright et al, 1987; Shah et al, 1992; Fernhout et al, 1997]. One study also reported evidence of familial CLL in association with breast cancer [Linet et al, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…One study also reported evidence of familial CLL in association with breast cancer [Linet et al, 1989]. Shah et al [1992] reported the cases of three of six siblings in whom CLL developed at ages 64, 67, and 68 years, while Fernhout et al [1997] described the cases of four siblings more than 80 years of age with CLL. All four of the latter siblings showed clonal chromosome aberrations, which were different in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The established relationship between HLA and Hodgkin's 51 Sibs M, M Sib M LK Videbaek 1958 52 Uncle, nephew Hudson et al 1960 53 Sibs M, M; Sibs M, M Gunz et al 1962 54 Sibs F, M, M Fitzgerald et al 55 Furbetta et al 1963 56 Grandparent M, parent F, offspring F Wisniewski 1966 57 Parent M, offspring M Rigby 1966 58 2 half-sibs Ardizzone et al 1968 59 Sibs M, M Magaraggia et al 1968 60 Sibs M, M McPhedran et al 1969 61 Sibs F, M, F, cousins F, M, M Fraumeni et al; 62 Blattner et al 1969 63 Sibs F, M, M Gunz et al 1969 64 Sibs M, F Sib CGL Sibs M, M Undritz et al 1971 65 Sibs M, M, M, F Potolosky et al 1971 66 Sibs F, F Sib LY, sib LY, sib acute LK Schweitzer et al 1973 67 Sibs F, M, M, F, F Blattner et al; 68 Neuland et al; 69 Shen et al; 70 Parent M, offspring M, M, F, F Caporaso et al 1991 71 Gunz 1975 72 3 first degree; 3 others Petzholdt 1976 73 Sibs M, M, M Fazekas et al 1978 74 Sibs, M, M, M Branda et al 1978 75 Parent F; offspring M Conley et al 1980 76 Sibs F, F Sibs M, M Nephew, maternal aunt; Nephew M; greataunt Alfinito et al 1982 77 Sibs F, F Vanni et al 1983 78 Sibs F, F Brok-Simoni et al 79 MZ twins F, F, sib F Hakim et al 1987 80 Eriksson et al 1987 81 Sibs M, M; Sibs M, F; Sibs M, F; MZ twins M; Parent M, offspring M; Parent M, offspring M Shah et al 1992 82 Sibs F, M, F Cuttner 1993 83 Sibs M, M; Sib M NHL Parent M, offspring M; MZ twins M, M Fernhout et al 1997 84 Sibs F, F, F, F Yuille et al 2000 9 Parent …”
Section: Molecular Genetics Of Familial Chronic Lymphocytic Leukemiamentioning
confidence: 99%